3, 4‐Ethylenedioxythiophene Functionalizationed with Tetrathiafulvalene: Synthesis and Selective Esterification. (7th February 2014) - Zhang, Lei; Wu, Changzhi; Wang, Chengyun; Zuo, Hujin; Shen, Yongjia
<x xml:space="preserve">Abstract</x> 3, 4‐(Hydroxymethyl‐ethylenedioxy)thiophene (4) and 3, 4‐(2′‐hydroxypropylenedioxy)thiophene (4'′) were synthesized from dimethyl 3, 4‐dihydroxythiophene‐2, 5‐dicarboxylate (1), which were isomers and difficult to separate. When they were esterified with tetrathiafulvalene carried carboxylic acid group, only 3, 4‐(hydroxymethyl‐ethylenedioxy)thiophene (4) could be esterified. No such selectivity was observed when the isomers were esterified by lauric acid and benzoic acid, respectively.